1994
DOI: 10.1111/j.1365-2249.1994.tb06013.x
|View full text |Cite
|
Sign up to set email alerts
|

Antineutrophil cytoplasm antibodies (ANCA) of IgA isotype in adult Henoch-Schönlein purpura

Abstract: SUMMARYANCA are associated with certain forms of systemic vasculitis, and have been reported previously to be of Ihe IgG and IgM isotype. We examined ihc possible association between IgA ANCA and the IgA-relaled diseases Henoch-Schonlein purpura (HSP) and IgA nephropaihy (IgAN). IgA and IgG ANCA were detected by isotype-specifie solid-phase assays with a erude neutrophil extract, and their presence was confirmed by antigen-specific fluid-phase competitive inhibition tests and by indirect inimunofiuorescence. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

1996
1996
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(10 citation statements)
references
References 22 publications
0
9
0
1
Order By: Relevance
“…With regard to mucosal manifestations in GPA, and as secretory IgA (SIgA) is the dominating isotype at mucosal sites, it is of interest to study IgA-and SIgA-class PR3-ANCA in relation to organ manifestations and disease activity in AAV. Circulating IgA-class PR3-ANCA has been described previously in GPA [25], and IgA-ANCAs have been observed in IgA vasculitis (formerly known as Henoch-Sch€ onlein purpura) [26], IgA-nephropathy [27], cutaneous vasculitis [28], liver cirrhosis [29] and inflammatory bowel diseases [30,31]. SIgA PR3-ANCA, however, has not been described previously in AAV.…”
Section: Introductionmentioning
confidence: 99%
“…With regard to mucosal manifestations in GPA, and as secretory IgA (SIgA) is the dominating isotype at mucosal sites, it is of interest to study IgA-and SIgA-class PR3-ANCA in relation to organ manifestations and disease activity in AAV. Circulating IgA-class PR3-ANCA has been described previously in GPA [25], and IgA-ANCAs have been observed in IgA vasculitis (formerly known as Henoch-Sch€ onlein purpura) [26], IgA-nephropathy [27], cutaneous vasculitis [28], liver cirrhosis [29] and inflammatory bowel diseases [30,31]. SIgA PR3-ANCA, however, has not been described previously in AAV.…”
Section: Introductionmentioning
confidence: 99%
“…It was reported that ANCA is also detectable in patients with HSP. However, the prevalence of HSP remains controversial, ranging 0%-79% [10][11][12][13] . It has been shown that the positive ANCA rate is as high as 82.3% [14] , suggesting that ANCA can be used to confirm the diagnosis of HSP in children.…”
Section: Discussionmentioning
confidence: 99%
“…Till now, most studies were confined to children, only a few studies have been done in adults [12,13] and no reports on adult HSP patients presenting mainly with gastrointestinal symptoms are available. The aim of this study was to evaluate the clinical significance of ANCA in adult HSP patients who presented mainly with gastrointestinal symptoms and its role in the diagnosis of HSP and its relationship to the disease severity.…”
Section: Discussionmentioning
confidence: 99%
“…In Kawasaki's disease, ANCA is infrequent [21]. In IgA-vasculitis (formerly known as Henoch-Schönlein purpura) there are reports of IgA-ANCA during episodes of active disease, but IgG-ANCA is rare [22].…”
Section: Other Forms Of Vasculitismentioning
confidence: 99%